Gradients and dynamics of inner bark and needle osmotic potentials in Scots pine (Pinus sylvestris L.) and Norway spruce (Picea abies L. Karst) - Paljakka, Teemu; Jyske, Tuula; Lintunen, Anna; Aaltonen, Heidi; Nikinmaa, Eero; Hölttä, Teemu (Wiley, 2017)
Preconditions of phloemtransport in conifers are relatively unknown. We studied the variation of needle and inner bark axial osmotic gradients and xylem water potential in Scots pine and Norway spruce by measuring needle and inner bark osmolality in saplings andmature trees over several periodswithin a growing season. The needle and inner bark osmolality was strongly related to xylem water potential in all studied trees. Sugar concentrations were measured in Scots pine, and they had similar dynamics to inner bark osmolality. The sucrose quantity remained fairly constant over time and position, whereas the other sugars exhibited a larger change with time and position. A small osmotic gradient existed from branch to stem base under pre-dawn conditions, and the osmotic gradient between upper stem and stem base was close to zero. The turgor in branches was significantly driven by xylem water potential, and the turgor loss point in branches was relatively close to daily minimum needle water potentials typically reported for Scots pine. Our results imply that xylem water potential considerably impacts the turgor pressure gradient driving phloemtransport and that gravitation has a relatively large role in phloem transport in the stems of mature Scots pine trees.
Keywords: nilakuljetus; osmoottinen vahvuus; turgor-paine; vesipotentiaali; conifer; phloem transport; turgor pressure; havupuut; nila; Pinophyta; osmolality; phloem; transport; turgor; xylem water potential